Prilaku Pencarian Informasi Pekerjaan oleh Masyarakat dengan Analisis Model Wilson - Rambe, Ingka Mutiara; Purwaningtyas, Franindya; Ramadani, Sri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Introduction This paper discusses people's information seeking behavior. In fact, many university graduates are still facing serious difficulties in the job search process given the increasing unemployment rate.Method of collecting data Purposive sampling was used with 10 respondents. Interviews were used as a data collection technique.Data analysis Miles and Huberman's data analysis was used in this study to reduce, present data and draw conclusions.Results and Discussion Two barriers in seeking information come from psychological factors and interpersonal skills. Fresh graduates with low psychological and interpersonal skills, such as lack of confidence, confusion, low self-esteem, anxiety, lack of communication show ineffective search results. Situations where information sources are easily accessible support faster information retrieval and vice versa. Our informants who live in cities with easy access support the information search process.Conclusion The factors that influence information seeking behavior are psychological situation, demographic situation, interpersonal skills, environment and characteristics of information sources. These five factors influence each other. Keywords: information behavior; information search; publik; job seekers